Cervical vertebral anomalies in skeletal malocclusions: A cross-sectional study on orthodontic patients at the Aga Khan University Hospital, Pakistan - Saman Faruqui; Mubassar Fida; Attiya Shaikh (Wolters Kluwer Medknow Publications, 2014)
Introduction: Morphological deviations of the cervical vertebral column have been described in relation to craniofacial aberrations and syndromes. Furthermore, it has recently been shown that abnormal morphology of upper cervical vertebrae is associated with malformation of the jaws and occlusion. Accordingly, it is relevant to focus on similar associations in patients with skeletal malocclusions. Therefore, the objectives of this study are to: Identify the anomalies of the cervical column in patients with skeletal malocclusionsDetermine the association between cervical vertebral anomalies and skeletal malocclusions. Materials and Methods: This cross-sectional study was conducted on a total of 90 subjects at the Aga Khan University Hospital, Pakistan. The inclusion criteria were: (1) Pakistani origin; (2) standardized pretreatment profile radiograph with first six cervical vertebrae visible; and (3) accessibility of the second-profile radiograph (mid- or posttreatment). The exclusion criteria were: (1) A prior history of orthodontic treatment; (2) any craniofacial anomaly; and (3) systemic muscle or joint disorder. Lateral cephalograms of all subjects (n = 90) were traced by the principal investigator and sagittal jaw relationship was assessed. A total of 30 subjects each with skeletal Class I, Class II, and Class III malocclusions were selected and the cervical vertebral anomalies were observed on their cephalometric radiographs. The frequencies of cervical vertebral anomalies according to skeletal malocclusion categories and gender were analyzed with the Chi-square test, whereas association of cervical vertebral anomalies with skeletal malocclusions was assessed with logistic regression analysis. The level of significance (P ≤ 0.05) was used for the statistical tests. Results: Most common anomaly observed in the three groups was fusion between C2 and C3 (P = 0.006). This anomaly was found in 20% of subjects with skeletal Class I, 50% of subjects with skeletal Class II and 53.3% with skeletal Class III malocclusions. The highest frequencies of partial cleft at the level of C1 and occipitalization were observed in subjects with skeletal Class II and III malocclusions, respectively. However, none of the subjects showed fusion between C1 and C2 or dehiscence. No statistically significant gender difference was found in the occurrence of morphological deviations of the cervical column. The association of cervical vertebral anomaly was found to be the highest with skeletal Class III and lowest with skeletal Class I malocclusions. Conclusion: Fusion between C2 and C3 seems to be the most commonly occurring anomaly. This anomaly seems to be more often associated with skeletal Class III than skeletal Class I or Class II malocclusions.